Prediction of pulmonary embolism and its complication in diabetes mellitus type 2: a 5-year retrospective study - Jasmina Bošnjić (Medicinski glasnik, 2023)
Aim: To investigate the association between type 2 diabetes mellitus (T2DM) and pulmonary embolism, as well as to determine the prognostic value of troponin, D-dimer, prothrombotic, and proinflammatory markers in patients with T2DM. Methods: The retrospective cohort study included 305 patients with pulmonary embolism, divided into two groups: the first group with type 2 diabetes mellitus (n=165) and the control group without type 2 diabetes mellitus (n=140). Data were collected from May 2018 to May 2023. In all patients the following parameters were analysed: anthropometric parameters, laboratory parameters (troponin, D-dimer, CRP, fibrinogen, uric acid, glucose, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides), arterial blood pressure, antiphospholipid antibodies, HOMA-IR index, CT angiography of the pulmonary artery, rate of adverse clinical events in pulmonary embolism (need for inotropic catecholamine support, fibrinolysis, cardiopulmonary resuscitation) and the rate of intrahospital mortality from pulmonary embolism. Results: Patients with T2DM had elevated troponin, D-dimer, CRP, uric acid, fibrinogen, HOMA-IR and more severe clinical complications with higher mortality rates within 10 days of hospital admission. Significant predictors of PE in T2DM patients were found. Patients with pulmonary embolism in T2DM had a 4.38 times higher chance of death compared to patients with pulmonary embolism without T2DM. Conclusions: Troponin, D-dimer, prothrombotic, and proinflammatory markers have good prognostic value for short-term outcomes in PE among patients with T2DM
Keywords: D-dimer; proinflammatory markers; prothrombotic markers; troponin